To quench our infinite thirst with some brand new, spanking-white, automatic uphill concrete rivers (Document Associates, 1976)
How do you create new water supplies? Today, billions of dollars are spent to move millions of gallons of water-for drinking, industry, irrigation. At present, irrigation consumes 60 per cent of the water taken from North American streams ; and water is now flowing where it has never gone before, in a system that eventually rival that of the earth's original rivers! This film shows some of the things that are being done to divert water, and how new techniques will affect our dams and reservoirs.